Host-Range Restriction of Vaccinia Virus E3L Deletion Mutant Can Be Overcome In Vitro, but Not In Vivo, by Expression of the Influenza Virus NS1 Protein - Guerra, Susana; Abaitua, Fernando; Martínez-Sobrido, Luis; Esteban, Mariano; García-Sastre, Adolfo; Rodríguez, Dolores (PLOS ONE, 2011)
During the last decades, research focused on vaccinia virus (VACV) pathogenesis has been intensified prompted by its potential beneficial application as a vector for vaccine development and anti-cancer therapies, but also due to the fear of its potential use as a bio-terrorism threat. Recombinant viruses lacking a type I interferon (IFN) antagonist are attenuated and hence good vaccine candidates. However, vaccine virus growth requires production in IFN-deficient systems, and thus viral IFN antagonists that are active in vitro, yet not in vivo, are of great value. The VACV E3 and influenza virus NS1 proteins are distinct double-stranded RNA-binding proteins that play an important role in pathogenesis by inhibiting the mammalian IFN-regulated innate antiviral response. Based on the functional similarities between E3 and NS1, we investigated the ability of NS1 to replace the biological functions of E3 of VACV in both in vitro and in vivo systems. For this, we generated a VACV recombinant virus lacking the E3L gene, yet expressing NS1 (VVΔE3L/NS1). Our study revealed that NS1 can functionally replace E3 in cultured cells, rescuing the protein synthesis blockade, and preventing apoptosis and RNA breakdown. In contrast, in vivo the VVΔE3L/NS1 virus was highly attenuated after intranasal inoculation, as it was unable to spread to the lungs and other organs. These results indicate that there are commonalities but also functional differences in the roles of NS1 and E3 as inhibitors of the innate antiviral response, which could potentially be utilized for vaccine production purposes in the future.